A Convenient Deoxygenation–Dimerization–[1+2]-Cycloaddition Synthetic Sequence from ω-Bromoalkylisatins to Indolin-2-onemethanofullerenes Bearing Isoindigo Moiety - Bogdanov, Andrei V.; Yusupova, Gulshat G.; Romanova, Irina P.; Latypov, Shamil K.; Krivolapov, Dmitry B.; Mironov, Vladimir F.; Sinyashin, Oleg G. (Synthesis, 2013)
An easy and convenient step-by-step synthetic procedure towards the design of a novel spiroindolomethanofullerene bearing an isoindigo fragment is reported.
Keywords: phosphorus; deoxygenation; carbenes; cycloaddition; fullerenes